Lipoprotein (a) testing patterns among subjects with a measured lipid panel: The Mayo Clinic experience - Matteo Manzato; Jeffery W. Meeusen; Leslie J. Donato; Allan S. Jaffe; Vlad C. Vasile (American Journal of Preventive Cardiology, 2024)
Objective: Lipoprotein(a) [Lp(a)] has been associated with Atherosclerotic Cardiovascular Disease (ASCVD). Approximately 20 % of the population has elevated Lp(a). Despite its well-recognized role in ASCVD, universal screening remains controversial. The aim of our study is to investigate laboratory testing patterns for Lp(a) in subjects screened with a standard lipid panel at a large tertiary referring US institution. Methods: Data were retrospectively collected at Mayo Clinic from the Mayo Data Explorer (MDE). Subjects were included if they had a lipid panel measured between May 1, 2022, and April 30, 2023. Demographic data, Lp(a) measurements, statins and aspirin prescription and ASCVD events which occurred at any time in the life of a subject were recorded along with respective dates. The cumulative number of Lp(a) laboratory test orders were also tallied from 1994 to 2023 independently of the lipid panel requests. Results: Between May 1, 2022, and April 30, 2023, 257,225 subjects had a lipid panel ordered. Of these, only 386 (0.15 %) had Lp(a) tested within 1 year of the lipid panel, while 2406 (0.94 %) had Lp(a) tested at any time. Lp(a) was tested more frequently in males (67 %) and in subjects who developed Myocardial Infarction (MI) at any time (12 %). Following Lp(a) results, there was no significant change in statin or aspirin prescription associated with Lp(a) levels. Secondary prevention was the main setting for ordering Lp(a) testing, and there was no change in this trend throughout the years. Conclusions: Testing rates for Lp(a) in the general population are low and the main setting remains secondary prevention. Women are less tested than men. When Lp(a) is found to be elevated, often times there is no change in patient management to mitigate the ASCVD risk.